2003
DOI: 10.1007/s00300-003-0541-9
|View full text |Cite
|
Sign up to set email alerts
|

Limnocalanus macrurus in the Kara Sea (Arctic Ocean): an opportunistic copepod as evident from distribution and lipid patterns

Abstract: Limnocalanus macrurus is an important member of the zooplankton communities of the Siberian shelf seas. During the cruise, Boris Petrov 1999, in August/ September to the southern Kara Sea and the Ob and Yenisej estuaries, its abundance and vertical distribution were investigated. In adults, salinity tolerance, egg production, feeding and lipid composition were studied. L. macrurus occurred in water with salinities ranging from 1.7 to >33 without clear preference, as revealed from salinity-tolerance experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 38 publications
(49 reference statements)
3
16
0
1
Order By: Relevance
“…Similar to our study, Hiltunen et al [21] reported high proportions of these fatty acids, especially EPA and DHA. Conversely, in the arctic Laptev and Kara Seas, much lower proportions of PUFAs have been reported [22,23] and were probably caused by high reliance on diatoms [21].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similar to our study, Hiltunen et al [21] reported high proportions of these fatty acids, especially EPA and DHA. Conversely, in the arctic Laptev and Kara Seas, much lower proportions of PUFAs have been reported [22,23] and were probably caused by high reliance on diatoms [21].…”
Section: Discussionmentioning
confidence: 88%
“…In L. macrurus, oil sac length has been used for the determination of the lipid content by Vanderploeg et al [8] in Lake Michigan, and by Dahlgren et al [6] in the Bothnian Bay. The quality of lipids in L. macrurus is poorly known, as the studies are few and they have mainly focused on populations that live in lakes [21] or in Arctic coastal waters [22,23]. In the Baltic Sea, the only study investigating the fatty acids of L. macrurus gives no information about their seasonal variation but indicates some differences from the lake populations of the same latitude [21].…”
Section: Open Accessmentioning
confidence: 99%
“…In the field, copepods likely had access to a variety of food items, since the presence of 18:0 and FA of the ω6 series point to grazing on protists or smaller animals, while odd-chain length and branched FA are good indicators of feeding on bacteria, and 16:1ω7 and EPA may result from feeding on diatoms (Kaneda 1991, Ederington et al 1995, Des vilettes et al. 1997b, Hirche et al 2003, Caramujo et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed the total FA that includes membrane FA, and although the latter are probably under metabolic control and thus weakly influenced by dietary FA (Desvilettes et al 1997b), yet it was possible to detect FA differences in total FA extracts that could be related to diet FA composition. In the field, copepods likely had access to a variety of food items, since the presence of 18:0 and FA of the ω6 series point to grazing on protists or smaller animals, while odd-chain length and branched FA are good indicators of feeding on bacteria, and 16:1ω7 and EPA may result from feeding on diatoms (Kaneda 1991, Ederington et al 1995, Des vilettes et al 1997b, Hirche et al 2003, Caramujo et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation